1975
DOI: 10.1128/iai.11.6.1261-1264.1975
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Transformation in Syphilis: an In Vitro Correlate of Immune Suppression In Vivo?

Abstract: Suppression of cellular immunity during primary and secondary infection may explain, in part, the unusual clinical evolution of syphilis. We have previously shown that lymphocytes from normal subjects undergo blastic transformation when exposed in vitro to Treponema refringens. This response was suppressed in patients with syphilis. the suppression being unrelated to serum factors. In the present paper we studied lymphocyte response in vitro to T. refringens, T. reiter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
2

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 10 publications
0
14
2
Order By: Relevance
“…Since T. reiteri can be readily cultivated in vitro and shares common group antigens with virulent T. pallidum, although their relationship to T. pallidum infectivity is unknown (14), it was used as a source oftreponemal antigen in our lymphocyte cultures. Musher et al (14,15) demonstrated depressed levels of blastogenesis to several treponemal organisms, including T. pallidum, T. refringens, and T. reiteri, in primary and secondary human syphilitics which, in part, contradicts our results. These inconsistencies may be due to different preparations or concentrations of antigen used.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Since T. reiteri can be readily cultivated in vitro and shares common group antigens with virulent T. pallidum, although their relationship to T. pallidum infectivity is unknown (14), it was used as a source oftreponemal antigen in our lymphocyte cultures. Musher et al (14,15) demonstrated depressed levels of blastogenesis to several treponemal organisms, including T. pallidum, T. refringens, and T. reiteri, in primary and secondary human syphilitics which, in part, contradicts our results. These inconsistencies may be due to different preparations or concentrations of antigen used.…”
Section: Discussioncontrasting
confidence: 96%
“…Although it has been suggested that T. pallidum infection in rabbits is an acute and selflimiting disease (15), the infectious spirochete localizes in the lymph nodes and remains there indefinitely as a form of latency (3). Schell and Musher (22) detected evidence of nonspecific cell-mediated immunity as measured by partial protection to Listeria monocytogenes in rabbits 3 to 6 weeks after T. pallidum infection.…”
mentioning
confidence: 99%
“…Similar immunodynamics, whereby immunodeficiency is followed by periods of hypersensiliviiy. have been implicated in other infectious diseases including syphilis (Strugnell et al 1984, Musher et al 1975, leishmaniasis (Reiner & Finke 1983. Scott &.…”
Section: Immunosuppressjon In the Etiology/ Pathogenesis Of Periodontmentioning
confidence: 99%
“…The role of cell-mediated immunity in the host defense against syphilis remains unclear. There is substantial evidence that a state of anergy or immunosuppression exists in early syphilis (7,8,10,11,18), which is consistent with negative skin reactions to Treponema pallidum in primary and secondary syphilitics (6,9). A decreased number of lymphocytes in the paracortical areas of lymph nodes has also been found in early disease (15).…”
mentioning
confidence: 91%